(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In 2023, the media continues to lack an understanding of the limits when it comes to disclosing sensitive information regarding an ongoing court case. This article is a demonstration by researchers on the impact of media trials on various parties involved in a case. A case in August 2022, brought before the Madras High Court, has spurred researchers to reevaluate the phenomenon of media trials and their consequences for the accused, victims, and witnesses. The Contempt of Courts Act, 1971, was enacted with the purpose of addressing media interference in the administration of justice. The experts have also underscored the media’s sway over the judgments of judges in certain instances. This article also discusses the incorporation of the rights to freedom of the press and a fair trial, as well as the potential conflicts that may arise when one person’s rights impede another’s. Several rulings have emphasized the necessity of maintaining an equilibrium between the rights of two individuals. This article also examines the establishment of the Witness Protection Scheme and its connection to safeguarding the anonymity of witnesses involved in a case. Lastly, the researchers conclude by summarizing previous jurist collective views on safeguarding confidential data from an ongoing project